Selected traditional Chinese herbal medicines for the treatment of atopic dermatitis - research progress on the effect and mechanism of actions - Zhang, Lingjie; Lin, Hangjuan; Chen, Ninggang; Zhu, Suyan; Hu, Ying (Frontiers in Pharmacology, 2025)
Atopic dermatitis (AD) is a common chronic, recurrent, inflammatory skin disease characterized by pruritus, lichen-like changes and dry skin. Due to the complex pathogenesis of AD, its mechanism is primarily associated with genetic, skin barrier dysfunction, environmental, and immune factors. AD has been routinely treated with glucocorticoids, antihistamines, local immunomodulators, biological agents, and small molecules; however, the side effects are significant, and the treatment efficacy is limited. In recent years, traditional Chinese medicine (TCM) has gradually been widely used in the treatment of AD. Many studies have shown that TCM mainly regulates inflammatory cytokines, gut microbiota and the immune system. Therefore, it plays a crucial role in the treatment of AD. The treatment of atopic dermatitis using TCM is characterized by targeting multiple pathways and multiple targets, and it demonstrates significant therapeutic effects. This paper reviews the pathogenesis of AD and reports the efficacy of TCM on AD (including TCM prescription, single TCM, treatment of TCM metabolites), which provides a theoretical basis for TCM treatment of AD. TCM has certain therapeutic effects on AD. It can alleviate and treat AD in various ways. We should base our differentiation on syndrome differentiation and treatment differentiation. With the help of modern medicine, the clinical efficacy of TCM in treating AD can be improved.